ANALISIS KESALAHAN PEMAHAMAN KAMOSHIRENAI DAN DAROU PADA MAHASISWA PRODI PENDIDIKAN BAHASA JEPANG ANGKATAN 2018 UNIVERSITAS RIAU - Adam Islami Sakti; Arza Aibonotika; Dini Budiani (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: This study discussed error analysis on the comprehension of „kamoshirenai‟ and „darou‟ in Japanese Literature Study student batch 2018 in Riau University. The objective of this study is to examine the understanding of „kamoshirenai‟ and „darou‟ among students, as well as to detect the causal factor of its error in the comprehension of „kamoshirenai‟ and „darou‟. This research uses descriptive-quantitative as the basis for its method. Data collection was obtained by giving online questionnaires and quiz tests. The result indicates there are some errors in the etymology and context of „kamoshirenai‟ and „darou‟. Etymology error include the error in the adjective of „na-keiyoushi‟, „i-keiyoushi‟, verb, and noun. Meanwhile, error in the context includes sentences, adverbial, figurative impression and appropriation, possibility, and confirmation context. The causal factor on this comprehension of „kamoshirenai‟ and „darou‟ are specified into internal and external factors.Key Words: Error Analysis, „Kamoshirenai‟, „Darou‟, Japanese Modalities.